Prediction of cardiovascular events from systolic or diastolic blood pressure. Issue 6 (26th April 2022) - Talebi, Atefeh; Mortensen, Rikke Nørmark; Gerds, Thomas Alexander; Jeppesen, Jørgen Lykke; Torp‐Pedersen, Christian
Abstract: Over time, a focus on blood pressure has transferred from diastolic pressure to systolic pressure. Formal analyses of differences in predictive value are scarce. Our goal of the study was whether office SBP adds prognostic information to office DBP and whether both 24‐h ambulatory SBP and 24‐h ambulatory DBP is specifically important. The authors examined 2097 participants from a population cohort recruited in Copenhagen, Denmark. Cause‐specific Cox regression was performed to predict 10‐year person‐specific absolute risks of fatal and non‐fatal cardiovascular (CV) events. Also, the time‐dependent area under the receiver operator curve (AUC) was utilized to evaluate discriminative ability. The calibration plots of the models (Hosmer‐May test) were calculated as well as the Brier score which combines (discrimination and calibration). Adding both 24‐h ambulatory SBP and 24‐h ambulatory diastolic blood pressure did not significantly increase AUC for CV mortality and CV events. Moreover, adding both office SBP and office DBP did not significantly improve AUC for both CV mortality and CV events. The difference in AUC (95% confidence interval; p ‐value) was .26% (‐.2% to .73%; .27) for 10‐year CV mortality and .69% (‐.09% to 1.46%; .082) for 10‐year risk of CV events. The difference in AUC was .12% (‐.2% to .44%; .46) for 10‐year CV mortality and .04% (‐.35 to .42%; .85) for 10‐year risk of CV events. Moreover, for both CV mortality and CV events, office SBP did not improve prognostic information to office DBP. In addition, the Brier scores of office BP in both CV mortality and CV events were .078 and .077, respectively. Furthermore, the Brier scores were .077 and .078 in CV mortality and CV events of 24‐h ambulatory. For the average population as those participating in a population survey, the 10‐year discriminative ability for long‐term predictions of CV death and CV events is not improved by adding systolic to diastolic blood pressure. This finding is found for ambulatory as well as office blood pressure.